INNOVATION AT THE MARGINS: CREATIVE TECHNOLOGY ENTREPRENEURSHIP FOR INCLUSIVE DEVELOPMENT - Kim Minho; Park Jihoon; Lee Jiwon; Mardani Eka Ningrum (Yayasan Adra Karima Hubbi, 2026)
In emerging economies, marginalized communities face significant barriers to entrepreneurship, including limited access to resources, markets, and technology. Creative technology entrepreneurship offers an innovative solution to these challenges, empowering local entrepreneurs to create impactful businesses that drive social change. This study explores the role of creative technologies, such as mobile apps, digital media, and virtual reality, in enhancing community-based entrepreneurship and fostering inclusive development. The research aims to understand how these technologies enable marginalized entrepreneurs to overcome barriers, increase market access, and create sustainable business models. A mixed-methods approach was employed, combining qualitative case studies and quantitative surveys to assess the impact of technology adoption on business performance and social outcomes. The findings reveal that entrepreneurs who integrated creative technologies into their businesses saw significant improvements in customer engagement, market reach, and operational efficiency. Furthermore, social capital and local community networks played a crucial role in supporting technology adoption and fostering business success. The study concludes that creative technology entrepreneurship is a key driver of inclusive development, offering a pathway for marginalized communities to participate in the digital economy. These findings suggest that policymakers and development organizations should support the integration of creative technologies into entrepreneurship programs to promote sustainable economic and social growth.